Comparison of Hypnotic Suggestion and Transcranial Direct-Current Stimulation Effects on Pain Perception and the Descending Pain Modulating System: A Crossover Randomized Clinical Trial - Beltran Serrano, Gerardo; Rodrigues, Laura Pooch; Schein, Bruno; Souza, Andressa; Torres, Iraci L. S.; da Conceição Antunes, Luciana; Fregni, Felipe; Caumo, Wolnei (Frontiers in Neuroscience, 2019)
Abstract Objectives: This paper aims to determine if hypnotic suggestion analgesia and transcranial direct-current stimulation (tDCS) have a differential effect on pain perception. We hypothesized that tDCS would be more effective than hypnotic suggestion at changing the descending pain modulating system (DPMS), whereas the hypnotic suggestion would have a greater effect in quantitative sensory testing (QST). Design: This research was conducted as a randomized, blind and crossover trial. Settings: All the stages of this clinical trial were performed at the Laboratory of Pain and Neuromodulation of the Hospital de Clínicas de Porto Alegre. Subjects: Were included 24 healthy females aged from 18 to 45 years old, with a high susceptibility to hypnosis, according to the Waterloo-Stanford Group Scale of Hypnotic Susceptibility, Form C (15). Methods: The subjects received a random and crossover tDCS over the dorsolateral prefrontal cortex (DLPFC) (2mA for 20min) and hypnotic analgesia (20min). Results: Only hypnotic suggestion produced changes that are statistically significant from pre- to post-intervention in the following outcomes measures: heat pain threshold (HPT), heat pain tolerance (HPTo), cold pressure test (CPT) and serum brain-derivate-neurotrophic-factor (BDNF). The analysis showed a significant main effect for treatment (F=4.32; P=0.04) when we compared the delta-(Δ) of CPM task between the tDCS and hypnotic suggestion groups. Also, the change in the Δ-BDNF was positively correlated with the CPM task. Conclusions: The results confirm a differential effect between hypnotic suggestion and tDCS on the pain measures. They suggest that the impact of the interventions has differential neural mechanisms, since the hypnotic suggestion improved pain perception, whereas the tDCS increased inhibition in the DPMS. Registration information clinicaltrials.gov: NCT03744897. Perspective: These findings highlight the effect of hypnotic suggestion on contra-regulating mechanisms involved in pain perception, while the tDCS increased inhibition in the DPMS. They could help clinicians comprehend the mechanisms involved in hypnotic analgesia and tDCS and thus may contribute to pain and disability management. Keywords: Hypnotic analgesia, tDCS, Pain threshold, CPM, BDNF, Pain.